Impoverished recall of sensory details along infrequently travelled routes in aphantasia. - Li, Adrienne; Arrieta, Maria; Levine, Brian; Rosenbaum, R. Shayna (Memory, 2025)
Visual imagery is important for recalling environmental details, but individuals with aphantasia are reported to show intact spatial memory. We investigated spatial memories of previously experienced environments in individuals with and without aphantasia using self-report and route description tasks. Aphantasic participants (n = 113) and controls (n = 110) completed questionnaires on spatial navigation, memory, anxiety, and mood. A subgroup (aphantasic: n = 65, control: n = 72) completed a route description task assessing memory for details along frequently and infrequently travelled routes. Aphantasic participants did not differ significantly from controls on self-reported navigation ability or strategies. Both groups recalled similar numbers of spatial, entity, and sensory details when describing frequently travelled routes. However, aphantasic participants recalled fewer sensory details for infrequently travelled routes. This finding was corroborated by nominally lower ratings on self-reported memory for object locations and new routes. Findings suggest that spatial memory, including sensory content, remains intact in aphantasia for frequent routes. Impoverished sensory details for infrequent routes indicates that individuals with aphantasia may rely on compensatory strategies, like semanticization, for frequently experienced environments. This suggests that spatial memory for real-world environments involve dissociable processes, some of which are independent of imagery.